Partisipasi Orang Muda Katolik dalam Perayaan Ibadat Sabda Hari Minggu di Stasi St. Fransiskus Kaliorang - Robertus Raong; Hilario Didakus Nenga Nampar (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2022)
This study aimed to describe how the participation of young Catholics in the Sunday Service at St. Francis Xavier Multi-station Kaliorang, is seen from the forms of participation and the obstacles to their participation. This study uses a qualitative approach with a descriptive method. Based on the results of this study, it can be concluded that the forms of participation of young Catholics in the celebration of the Worship of the Word on Sundays consist of two forms, namely; (a) direct participation, and (b) indirect participation. Direct participation is being a choir officer, reading I and II, psalmist, the prayer of the people, song guide, order officer, and delivering offerings. Meanwhile, indirect participation is by being a parking attendant, cleaning the church environment, making altars, and providing moral and material support, especially from young Catholics who are already working. The direct participation rate from the calculation of the average answer to the questionnaire found 22 respondents (52.6%) with a high participation rate, 13 respondents (31.7%) moderate participation rate, 5 respondents (12.2%) low participation rate, and 1 respondent (2.4%) did not participate. Respondents' answers to indirect participation questions, obtained data from 17 respondents (41.5%) with high participation rates, 15 respondents (36.6%) moderate participation rates, 6 respondents (14.6%) low participation rates, and 3 respondents (7.3%) did not participate.